2017
DOI: 10.1007/s10151-017-1637-5
|View full text |Cite
|
Sign up to set email alerts
|

The importance of rectal washout for the oncological outcome after Hartmann’s procedure for rectal cancer: analysis of population-based data from the Swedish Colorectal Cancer Registry

Abstract: BackgroundDuring rectal cancer surgery the bowel may contain viable, exfoliated cancer cells, a potential source for local recurrence (LR). The amount and viability of these cells can be reduced using intraoperative rectal washout, a procedure that reduces the LR risk after anterior resection. The aim of this study was to analyse the impact of washout on oncological outcome when performed in Hartmann’s procedure (HP) for rectal cancer.MethodsA national cohort study on data for patients registered from 1995 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Hartmann's procedure has previously been associated with low major complication and mortality rates, and is often reserved for frailer patients. However, more recently the complication profile appears to have been quite high, with the frequency of pelvic abscesses ranging from 12 to 33 per cent, further increasing the risk of pelvic seeding after leakage of intraluminal contents from the distal rectal remnant. These findings perhaps point towards Hartmann's being a surrogate marker of, for example, fitness or frailty of a patient, but it is not possible to conclude this from the data in the present study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Hartmann's procedure has previously been associated with low major complication and mortality rates, and is often reserved for frailer patients. However, more recently the complication profile appears to have been quite high, with the frequency of pelvic abscesses ranging from 12 to 33 per cent, further increasing the risk of pelvic seeding after leakage of intraluminal contents from the distal rectal remnant. These findings perhaps point towards Hartmann's being a surrogate marker of, for example, fitness or frailty of a patient, but it is not possible to conclude this from the data in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…Hartmann's procedure may be an independent predictor of local recurrence owing to the risk of viable exfoliated cancer cells, capable of implanting, being present within the bowel lumen; these become a potential source of local recurrence due to incorporation into the staple line at the rectal stump. Hartmann's procedure has previously been associated with low major complication and mortality rates, and is often reserved for frailer patients. However, more recently the complication profile appears to have been quite high, with the frequency of pelvic abscesses ranging from 12 to 33 per cent, further increasing the risk of pelvic seeding after leakage of intraluminal contents from the distal rectal remnant.…”
Section: Discussionmentioning
confidence: 99%
“…The data indicated that the risk of LR was higher after perforation during APR compared with the other abdominal resection procedures, but the limited number of events in the cohort did not allow further subgroup analysis. However, as one indication for HP in rectal cancer surgery is adverse intraoperative events making anastomosis inappropriate, some of the perforations registered after HP might have been a consequence of incidental perforation when the primary intention was AR 22 . Unfortunately, the SCRCR does not contain data on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, several studies have demonstrated no clear efficacy of rectal washout in preventing local recurrence [6,[17][18][19][20]. For instance, Terzi et al conducted a prospective clinical study on 96 patients with colorectal cancer undergoing anterior resection and concluded that rectal washout did not decrease the rate of local recurrence [6].…”
Section: Discussionmentioning
confidence: 99%